Vestígios ambientais de embalagens de agrotóxicos: uma análise da relação pessoa-ambiente no contexto rural sob a perspectiva da teoria bioecológica - Cardoso, Ruana Michela Santos (2022)
The generation of empty pesticide containers, followed by improper disposal, has become a major concern in recent years due to the expansion of the use of pesticides in agriculture together with the dismantling of socio-environmental policies. Pesticides packaging is considered dangerous and, when improperly disposed of, and/or reused, can result in severe negative externalities to human health and the environment. In this study, the issue of disposal of pesticide packaging is articulated from the person-environment relationship based on the Bioecological Theory for presenting a systemic analysis around socio-environmental issues. Added to this theory, the concept of ecological contexts was used, consisting of the microsystem and the mesosystem, proposed by Bronfenbrenner (2005). The present research has the following question: does the disposal of pesticide packaging in the studied community offer socio-environmental risks to the proximal ecological contexts? The purpose is to investigate the behavior of disposal of pesticide packaging from the traces found, treating this as a socioeconomic-environmental problem that affects rural areas. This is an exploratory and descriptive study with a quantitative approach, based on the technique of environmental traces, which is centered on the environment and involves the identification of traces linked to human action in the environment. The area for data collection was divided into four quadrants (A, B, C and D), where the following criteria were used for the definition: prevalence of residences, agricultural areas (including irrigated cultivation) and presence of water bodies. For data collection, an observation form and photographic records were used. The behavioral traces technique is a non-intrusive method, based on observation, through which it was possible to identify 18 different types of pesticide packages, being 72.2% in Quadrant A, 22.2% in Quadrant B and 5, 6% in Quadrant D, not occurring in Quadrant C. Similarities were found in the quadrants, such as the predominance of irrigated cultivation and tomato production. The results indicate that the rigid and flexible pesticide packages were placed close to the workplace, residence and cafeteria, being constituted by the microsystem, and the relationship between people in these environments is linked to the mesosystem. In general, we suggest the development of intervention actions that develop an environment that facilitates pro-environmental behaviors aimed at the disposal of RSP so that serious damage to health and the environment can be avoided.